Impact of Glycemic Control, Biochemical Parameters, and Diabetes Duration on Xerostomia in Diabetic Patients - Nizam Ul Afreen; Anita Haroon; Saima Rehman; Naheed Akhtar; Samina Mohyuddin; Syed Zaryab Ahmed (Pakistan Journal of Medicine and Dentistry)
Background: Xerostomia, or dry mouth, is a common condition among diabetic patients, potentially affecting their quality of life. The study aimed to investigate the prevalence of xerostomia and its association with various demographic, medical, and biochemical variables.